2015
DOI: 10.1038/sj.bdj.2015.440
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre, multicycle audit of the prescribing practices of three paediatric dental departments in the North of England

Abstract: Results revealed deficiencies in prescribing practices in all three centres. Following education and the provision of an aide-memoire in subsequent cycles, improvements were seen in appropriateness of prescribing, increasing from 28% in the first cycle, to 71% in the third cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, merely listing practices to avoid does not solve the LVC problem (12). Other types of interventions that have been studied include clinical decision support (13), provider feedback (14), educational interventions for clinicians (15) and patients (16), and nancial incentives (17). In their systematic review, Colla et al (18) found that the most common intervention was clinical decision support and showed that there is considerable evidence for the effectiveness of clinical decision support and provider feedback.…”
Section: Different Attempts Have Been Made To Decrease the Use Of Lvcmentioning
confidence: 99%
“…However, merely listing practices to avoid does not solve the LVC problem (12). Other types of interventions that have been studied include clinical decision support (13), provider feedback (14), educational interventions for clinicians (15) and patients (16), and nancial incentives (17). In their systematic review, Colla et al (18) found that the most common intervention was clinical decision support and showed that there is considerable evidence for the effectiveness of clinical decision support and provider feedback.…”
Section: Different Attempts Have Been Made To Decrease the Use Of Lvcmentioning
confidence: 99%
“…However, merely listing practices to avoid does not solve the LVC problem [8]. Other types of strategies that have been studied include clinical decision support [9], provider feedback [10], education for clinicians [11] and patients [12], and financial incentives [13]. In their systematic review, Colla et al [14] found that the most common strategy was clinical decision support and showed that there is considerable evidence for the effectiveness of clinical decision support and provider feedback.…”
Section: Introductionmentioning
confidence: 99%
“…14 Of all of the included studies, only 9 were dedicated to dental specialty groups. [15][16][17][18][19][20][21][22][23] The specialties included oral and maxillofacial surgery (n = 4), 16,20,21,23 endodontics (n = 2), 15,18 pediatric dentistry (n = 2), 17,19 and periodontics (n = 1) 22 ; no studies were focused on dental public health, oral and maxillofacial pathology, oral and maxillofacial radiology, orthodontics and dentofacial orthopedics, or prosthodontics. Furthermore, 8 of the 9 studies were crosssectional surveys, which prevents evaluation of antibiotic prescribing trends over time.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 8 of the 9 studies were crosssectional surveys, which prevents evaluation of antibiotic prescribing trends over time. [15][16][17][18][19][20][21][22] Despite the limitations, previous studies of antibiotic prescribing patterns among dental specialists had important findings. In 1 study of pediatric dentists, 30% reported prescribing antibiotics for a prolonged duration (10 days), and 15% reported prescribing antibiotics for dental pain.…”
Section: Discussionmentioning
confidence: 99%